A paediatric case of non-tuberculous mycobacterial infection in the neck. Issue 10 (October 2022) - McGenity, Clare; Dekany, Katalin; Stahlschmidt, Jens
Abstract: We discuss a case of rapid onset neck swelling in a paediatric patient with an underlying Mycobacterium avium infection. Surgical excision of the tissue revealed epithelioid granulomata with central caseating necrosis, background chronic inflammation and scanty acid-fast bacilli. Diagnosis of non-tuberculous mycobacterial infection can be reached using histological features, cultures and molecular techniques. Granulomatous inflammation has a range of infective and non-infective causes to consider when determining a diagnosis.